The Influence Of Compensation And Flexible Working Hours On The Perpormance Of Goride Driver Partners At PT. Gojek Indonesia (Survey Of Goride Driver Partners In The City Of Tasikmalaya): Sari Nurhayati, Barin Barlian, Titin Patimah - Nurhayati, Sari; Barlian, Barin; Patimah, Titin (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the effect of compensation and flexible working hours on the performance of driver partners in Tasikmalaya City. The research method used is a quantitative descriptive analysis method. The population in this study were goride driver partners in the city of Tasikmalaya. The sample in this study amounted to 100 people using accidental sampling technique. Data collection was carried out by distributing questionnaires. The analysis technique used is multiple linear regression analysis. The results of this research show that compensation and flexible working hours have a simultaneous and significant effect on driver performance. Meanwhile, compensation has a partial and significant effect on performance, and flexible working hours have a partial and significant effect on the performance of driver partners in the city of Tasikmalaya.